EMERGING POLITICAL DYNAMICS: AUTHORITARIANISM, DEMOCRACY, DIPLOMACY, AND NATION-BUILDING IN THE 21ST CENTURY (International journal of artificial intelligence, 2024)
The global political landscape is undergoing significant transformations, with the rise of authoritarian trends challenging democratic frameworks and reshaping nation-building processes. This paper explores the complex interplay between authoritarianism, democracy, diplomacy, and nation-building in the contemporary political environment. Authoritarian regimes, driven by populism and nationalism, have been consolidating power, undermining democratic institutions and principles. In contrast, democracies continue to face internal pressures, such as polarization and economic inequality, but show resilience through reforms and civic engagement. Diplomacy plays a pivotal role in managing these tensions, fostering international cooperation, and advocating for human rights. Nation-building processes, influenced by both political systems, are increasingly focused on social cohesion and the balancing of diverse national identities. The paper concludes by highlighting the need for adaptive governance, robust diplomatic frameworks, and inclusive nation-building strategies to navigate the evolving political landscape.